Implementing a rapid geographic range expansion - the role of behavior changes - Logan, Corina; McCune, Kelsey; LeGrande-Rolls, Christa; Marfori, Zara; Hubbard, Josephine; Lukas, Dieter (Peer Community Journal)

(untitled)
It is generally thought that behavioral flexibility, the ability to change behavior when circumstances change, plays an important role in the ability of species to rapidly expand their geographic range. Great-tailed grackles (Quiscalus mexicanus) are a social, polygamous species that is rapidly expanding its geographic range by settling in new areas and habitats. They are behaviorally flexible and highly associated with human-modified environments, eating a variety of human foods in addition to foraging on insects and on the ground for other natural food items. They offer an opportunity to assess the role of behavior change over the course of their expansion. We compared behavior in wild-caught grackles from two populations across their range (an older population in the middle of the northern expansion front: Tempe, Arizona, and a more recent population on the northern edge of the expansion front: Woodland, California) to investigate whether certain behaviors (flexibility, innovativeness, exploration, and persistence) have higher averages and variances in the newer or older population. We found that grackles in the edge population had a higher flexibility variance (measured by reversal learning) and a higher persistence average (they participated in a larger proportion of trials), and that there were no population differences in average levels of flexibility, innovativeness (number of loci solved on a multiaccess box), or exploration (latency to approach a novel environment). Our results elucidated that individuals differentially expressing a particular behavior in an edge population could facilitate the rapid geographic range expansion of great-tailed grackles, and we found no support for the importance of several traits that were hypothesized to be involved in such an expansion. Our findings highlight the value of population studies and of breaking down cognitive concepts into direct measures of individual abilities to better understand how species might adapt to novel circumstances.